Some thoughts and proposals for a way forward - Piñeiro, Valeria; Piñeiro, Martín (2017)
There is growing consensus that globalization, expansion of international trade, and rapid technological changes have favored developing countries more than developed ones. One clear example of this trend is the rapid Gross Domestic Product (GDP) growth rates experienced by developing countries compared to the growth rates experienced by more developed countries like Europe, the US, or Japan This unexpected result has turned many projections of world development on their head and shifted the political thinking in many countries. One of the main consequences has been the growth of populist forces in a number of developed countries, as well as an increase in protectionist sentiments and policies around the world.